Analysis of Factors Associated with the Severity of Acute Pancreatitis according to Etiology. (7th December 2017) - Kim, Dae Bum; Chung, Woo Chul; Lee, Ji Min; Lee, Kang-Moon; Oh, Jung Hwan; Jeon, Eun Jung
Abstract : Background . The objective of this study was to determine the factors associated with severity of acute pancreatitis (AP) according to two major etiologies: alcohol and gallstones. Methods . We reviewed the medical records of consecutive patients who were admitted with AP between January 2003 and January 2013. A total of 905 patients with AP (660 alcohol-induced, 245 gallstone-induced) were enrolled. Among them, severe AP (SAP) occurred in 72 patients (53 alcohol-induced, 19 gallstone-induced). Contributing factors between patients with and without SAP were analyzed according to the etiology. Results . Multivariate analysis demonstrated that current smoking, pancreatic necrosis, and bacteremia were associated with AP severity in both alcohol- and gallstone-induced AP. Pancreatic fluid collection was significantly associated with alcohol-induced SAP (p = 0.04 ), whereas dyslipidemia was significantly associated with gallstone-induced SAP (p = 0.01 ). Body mass index was significantly correlated with the Bedside Index of Severity in Acute Pancreatitis score in both alcohol- and gallstone-induced AP (p = 0.03 and 0.01, resp.). Conclusions . Current smoking, pancreatic necrosis, and bacteremia can aggravate the clinical course of AP. Pancreatic fluid collection and dyslipidemia were associated with AP severity according to the different etiologies. Obesity may also be associated with AP severity in both etiologies.